Inter-individual variability of social perception and social knowledge impairments among patients with schizophrenia. (August 2020) - Kitoko, Germain Manzekele Bin; Maurage, Pierre; ma Miezi, Samuel Mampunza; Gillain, Benoit; Kiswanga, Alain Pierre; Constant, Eric
Abstract: Deficits in social perception and knowledge and their negative impact on social functioning, have been repeatedly reported among patients with schizophrenia. However, earlier studies have focused on an overall assessment of social perception and social knowledge, without exploring their sub-components nor the interindividual variation of the deficit. This study aims to refine the exploration of this deficit and to assess its interindividual variation. Twenty-nine patients with schizophrenia and 24 healthy controls, matched for age and gender, completed a validated and integrated social perception and knowledge task (i.e. the PerSo test). Patients with schizophrenia had reduced performance in all PerSo subtests, namely contextual fluency, interpretation and social convention. However, these deficits were not correlated with the severity of clinical symptoms, and individual profiles analyses showed a marked heterogeneity among patients on their abilities. Our study confirms the existence of deficits in social perception and knowledge and underlines their considerable heterogeneity. Therefore, it is necessary to test and rehabilitate individually social perception and knowledge.